Anti Diabetic Activity of Methanolic and Chloroform Extracts of Solanum seaforthianum In Alloxan Induced Diabetes Rats: Pharmaceutical Science-Pharmacology - Gupta Atyam, V S S S; Rama Rao, Nadendla (International Journal of Life Science and Pharma Research, 2022)
Diabetes mellitus is a syndrome characterized by elevated glucose levels, polyurea, polydipsia and weakness due to insufficient entry of available glucose into the cells of the body. There are many allopathic drugs available to manage diabetes such as Sulfonylureas, biguanides, gliptins etc., but associated with hypoglycemia, sweating, dizziness, confusion, hunger, weight gain on long term usage and tolerance will be developed which are further treated using multiple drugs. According to our ancient system of medicine there are many medicinal plants available to treat diabetes with the same potency of allopathic drugs. Natural products are considered to be an effective alternative for the treatment and management of diabetes, because of higher efficacy which initiated the present study of anti diabetic activity of Solanum seaforthianum in an alloxan induced diabetes male albino rat. Diabetes was successfully induced with the help of alloxan at a dose of 120 mg/kg body weight and the animals which are possessing the glucose levels more than 250 mg/dL included in the study. Diabetic induced rats were treated with methanolic and chloroform extracts (200 and 400 mg/kg/kg body weight) of Solanum seaforthianum for 10 days. The collected blood samples on 1st, 4th, 7th, and 10th day were used to determine serum biochemical parameters such as cholesterol, triglycerides, low-density lipoprotein (LDL), high-density lipoprotein (HDL) cholesterol, urea, creatinine and total protein. Results: The treatment with extracts of Solanum seaforthianum significantly reduced the elevated blood glucose levels and reversed other altered parameters of Cholesterol, Triglycerides, HDL, LDL, Urea, Creatinine and Total Protein. Among the two extracts of Solanum seaforthianum chloroform extract has shown comparatively significant (p<0.001) anti diabetic activity in alloxan induced diabetes in albino rats. , , , ,